The Cytosolic Iron-Sulfur Cluster Assembly Protein MMS19 Regulates Transcriptional Gene Silencing, DNA Repair, and Flowering Time in Arabidopsis - Han, Yong-Feng (Public Library of Science, 2015)

(untitled) (PLoS One)
MMS19 is an essential component of the cytoplasmic iron-sulfur (Fe-S) cluster assembly complex in fungi and mammals; the mms19 null mutant alleles are lethal. Our study demonstrates that MMS19/MET18 in Arabidopsis thaliana interacts with the cytoplasmic Fe-S cluster assembly complex but is not an essential component of the complex. We find that MMS19 also interacts with the catalytic subunits of DNA polymerases, which have been demonstrated to be involved in transcriptional gene silencing (TGS), DNA repair, and flowering time regulation. Our results indicate that MMS19 has a similar biological function, suggesting a functional link between MMS19 and DNA polymerases. In the mms19 null mutant, the assembly of Fe-S clusters on the catalytic subunit of DNA polymerase α is reduced but not blocked, which is consistent with the viability of the mutant. Our study suggests that MMS19 assists the assembly of Fe-S clusters on DNA polymerases in the cytosol, thereby facilitating transcriptional gene silencing, DNA repair, and flowering time control.